2020
DOI: 10.1002/rmb2.12354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the one‐carbon metabolism on oocyte maturation, fertilization, embryo quality, and subsequent pregnancy

Abstract: One-carbon metabolism (OCM) refers to a metabolic pathway composed of folic acid (FA) and methionine metabolism. Methionine is an essential amino acid required for methylation, DNA synthesis, and protein synthesis, and coenzymes, such as vitamin B6, vitamin B12 (VB12), and FA, are necessary for normal methionine metabolism. Incomplete metabolism and disturbed equilibrium (balance) can result in harmful homocysteine (Hcy) accumulation. Hyperhomocysteinemia affects various stages of reproduction and is related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“… Hemmings et al (2013) reported that the developmental competence of oocytes is associated with amino acid turnover capacity. Akamine et al (2021) confirmed that fertilization, embryo quality, and clinical pregnancy could be affected by one-carbon metabolism in follicular fluid. Moslehi et al (2021) revealed that serum concentrations of 29 metabolites, including serine, were positively correlated with the annual rate of AMH decline.…”
Section: Discussionmentioning
confidence: 56%
“… Hemmings et al (2013) reported that the developmental competence of oocytes is associated with amino acid turnover capacity. Akamine et al (2021) confirmed that fertilization, embryo quality, and clinical pregnancy could be affected by one-carbon metabolism in follicular fluid. Moslehi et al (2021) revealed that serum concentrations of 29 metabolites, including serine, were positively correlated with the annual rate of AMH decline.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, exposure of trophoblast cells to elevated homocysteine may also increase cellular apoptosis and lead to inhibition of trophoblastic function, which is essential for successful placentation [ 3 , 29 ]. Folate and homocysteine are thought to be present in the follicular fluid [ 30 ], proportionally to the circulating levels. If folate and homocysteine are present in the microenvironment of the maturing oocyte, it is possible that an excess of homocysteine, or a deficiency of folate, could compromise oocyte competence in development and early embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the lack of information on mono-follicular fluid vitamin concentrations, but this datum appears irrelevant, as previously reported [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in S-adenosyl-methionine could lead to impaired DNA methylation, which may alter foetal metabolic programming and increase the risk of non-communicable diseases later in life ( Randunu & Bertolo 2020 ). Therefore, a deficiency in B12 may result in homocysteine accumulation and decreased circulating methionine, affecting reproduction, protein and DNA methylation ( Akamine et al 2021 ).
Figure 2 Formation of S-adenosyl-methionine and succinyl-CoA with vitamin B12 as coenzyme.
…”
Section: Impact Of Vitamin B12 On Reproductive Health Of Women Living...mentioning
confidence: 99%